Endoscopic-Assisted Radial Forearm Free Flap Harvest: A Novel Technique to Reduce Donor Site Morbidity - Van Kouwenberg, Emily A.; Yan, Alan; Patel, Ashit; McLaughlin, Rick L.; Northrup, Patricia; Cintron, Melanie; Agag, Richard L. (Journal of Reconstructive Microsurgery, 2019)
Background The radial forearm free flap (RFFF) remains a workhorse flap but can have significant donor site morbidity. The authors developed a novel technique for endoscopic-assisted RFFF (ERFFF) harvest and hypothesized improved donor site morbidity.Methods A retrospective cohort study was conducted evaluating patients who underwent ERFFF or RFFF by a single surgeon for head and neck reconstruction between November 2011 and July 2016; outcomes and complications were compared. A telephone survey was conducted to assess patient satisfaction with donor site appearance and function.Results Twenty-seven ERFFF and 13 RFFF harvests were performed. The cephalic vein was less commonly incorporated in ERFFF patients compared with RFFF patients (3.70 and 38.46%, respectively, p = 0.0095). ERFFF patients had lower rates of wound healing complications (0% vs. 15.38%, p = 0.10) and perfusion-related complications than RFFF patients (3.70% vs. 23.08%, p = 0.092). Fewer ERFFF patients reported a desire for a more normal appearance (42.86% vs. 71.43%, p = 0.361). The ERFFF group had a higher functional score (64.29% vs. 44.44%, p = 0.101), reporting lower rates of associated discomfort (35.71% vs. 85.71%, p = 0.063). None of the differences in rates of complications or patient-reported outcomes between the groups reached statistical significance.Conclusion ERFFF is safe and effective alternative to RFFF, with similar operative time, similar pedicle safety, and elimination of the lengthy forearm incision. Unnecessary cephalic vein dissection can be avoided with endoscopic visualization of the venae comitantes. Further research with a larger sample size and better standardization is needed to assess effects on donor-site morbidity.
Keywords: radial forearm; endoscopic; morbidity